The fiction writer [large type] - Cantor, Jillian (Thorndike Press large print dynamic drama., 2023)
"The once-rising literary star Olivia Fitzgerald is down on her luck. Her most recent novel--a retelling of Daphne du Maurier's Rebecca--was a flop, her boyfriend of nine years just dumped her and she's battling a bad case of writer's block. So when her agent calls her with a high-paying ghostwriting opportunity, Olivia is all too willing to sign the NDA. At first, the write-for-hire job seems too good to be true. All she has to do is interview Henry "Ash" Asherwood, a reclusive mega billionaire, twice named People's Sexiest Man Alive, who wants her help in writing a book that reveals a shocking secret about his late grandmother and Daphne du Maurier. But when Olivia arrives at his Malibu estate, nothing is as it seems. The more Olivia digs into his grandmother's past, the more questions she has--and before she knows it, she's trapped in a gothic mystery of her own" --